An untraceable and anonymous password authentication protocol for heterogeneous wireless sensor networks. (15th February 2018) - Amin, Ruhul; Islam, S.K. Hafizul; Kumar, Neeraj; Choo, Kim-Kwang Raymond
Abstract: Ensuring secure access to sensitive information in a wireless sensor networks (WSNs) remains a topic of ongoing research challenge, partly due to the wide range of potential attacks and attack vectors. In this paper, we reveal a previously unpublished vulnerability in the authentication scheme for ad hoc WSN of Chang et al. ' s. Specifically, we reveal that the authentication phase of the scheme does not defend against various known attacks. We then propose a robust authentication scheme for WSNs, designed to provide security against known active and passive attacks. We then evaluate the performance of the proposed scheme using AVISPA. Highlights: An untraceable and anonymous password authentication protocol. Robust authentication scheme for heterogeneous wireless sensor networks. Low-power sensor nodes for heterogeneous wireless sensor networks. Protocol verification using AVISPA.